Secagem em camada de espuma (foam mat drying) das folhas do mastruz (Chenopodium ambrosioides L.) - Moraes, Maria Rayanne Lima de (2021)
Chenopodium ambrosioides L. popularly known in Brazil as mastruz or Santa Maria is a medicinal plant whose scientific investigations around the world attribute several pharmacological activities to it, highlighting the leaves for their traditional use in the form of teas. However, the shelf life of the leaves quickly deteriorates after harvest and one of the conservation alternatives is the production of powder by the foam mat drying method, a simple and low cost alternative. Thus, this work aimed to examine the drying process of mastiff leaves by the foam mat drying method, using Portogel® as a foaming agent. The methodology of complete factorial experimental planning of 2³ + 3 central points was used, seeking to verify the influences of the independent variables: emulsifier concentration (3, 5 and 7%), agitation time (3, 5 and 7 min) and drying air temperature (50, 60 and 70 °C) on the dependent variable: drying time. The physical characterizations of the epazote leaf foam were performed: density, percentage of expansion, air incorporation capacity, foam stability, pH, titratable acidity and humidity. With the data from the drying kinetics it was possible to implement the adjustments to the non-linear mathematical models and with the powders obtained the water activity analysis was performed. For the statistical treatment it was verified that only the temperature presented significant influence on the drying time for a 95% confidence level. The drying curves presented a long period of constant rate and a short period of decreasing rate. The mathematical model that presented the best fit was Page's, which achieved higher correlation coefficients and lower residual quadratic sums at all temperatures studied (R² ≥ 0.9546, SQ ≤ 0.2149). The drying process of Chenopodium ambrosioides L. by the foam layer drying method proved to be feasible, being the condition of temperature of 70 ºC, emulsifier concentration of 3% and stirring time of 7 min the one that presented the shortest drying time (110 min) and water activity below 0.6. In the literature there is a lack of studies showing various drying parameters for mastiff in various process configurations.